Annual review of addictions and offender counseling. best practices - Lassiter, Pamela S.; Buser, Trevor J. (Resource Publications, 2017)
The Annual Review of Addictions and Offender Counseling, Best Practices: Volume III is the third volume in a series of peer-reviewed, edited books sponsored by the International Association of Addiction and Offender Counselors (IAAOC), a division of the American Counseling Association (ACA). Continuing the mission of the first two volumes, this volume provides a forum for publications addressing a broad array of topics in the field of addictions and offender counseling. Experts in the profession present innovative strategies and recommendations for best practices in drug education, intervention strategies, multicultural considerations, and counselor education. -- Publisher's website.